The implementation of guided discovery learning method to improve student learning outcomes at electromagnetic control system and operation course - Aswardi, Aswardi (COUNS-EDU: The International Journal of Counseling and Education, 2017)
This research is triggered by the learning process that is still yet to direct the active role of students learning. Based on the result of observation that the teacher is more dominant in the activity of learning than the students due to the students were lack of understanding towards the subject matter resulted in the lack of activeness of students in the classroom.  Based on the background study, it is needed to apply a method of learning that is able to enhance students’ activity and improving the score. One of them by applied the guided discovery learning method. The goal of this research is to know the learning outcomes improvement of the students when using guided discovery learning method on operated Electromagnetic Control System and Operation course in SMK Muhammadiyah Padang. The type of this research is quasi-experimental with one group pre-test post-test design. The population of this research was second year student of group one that registered at 2015/2016 academic year which 26 person of students. The instruments of research was objective tests that has been conducted a test of the validity, reliability, the difficulty level and the different index level. The data were analyzed by using gain score test. Based on the result, the students who achieve value of minimum completeness criteria (MCC) before using the guided discovery learning method was 7,7%. While the students who achieve minimum completeness criteria after using guided discovery learning method was 87,46%. Based on gained score test, the score of the students were increase in Middle Category. So, the implementation of guided discovery learning method can improve student learning outcomes on Electromagnetic Control System and Operation courses.